3D genome mapping identifies subgroup-specific chromosome conformations and tumor-dependency genes in ependymoma - Okonechnikov, Konstantin; Camgöz, Aylin; Chapman, Owen; Wani, Sameena; Park, Donglim Esther; Hübner, Jens-Martin; Chakraborty, Abhijit; Pagadala, Meghana; Bump, Rosalind; Chandran, Sahaana; Kraft, Katerina; Acuna-Hidalgo, Rocio; et al. (Nature Communications, 2023)
Ependymoma is a tumor of the brain or spinal cord. The two most common and aggressive molecular groups of ependymoma are the supratentorial ZFTA-fusion associated and the posterior fossa ependymoma group A. In both groups, tumors occur mainly in young children and frequently recur after treatment. Although molecular mechanisms underlying these diseases have recently been uncovered, they remain difficult to target and innovative therapeutic approaches are urgently needed. Here, we use genome-wide chromosome conformation capture (Hi-C), complemented with CTCF and H3K27ac ChIP-seq, as well as gene expression and DNA methylation analysis in primary and relapsed ependymoma tumors, to identify chromosomal conformations and regulatory mechanisms associated with aberrant gene expression. In particular, we observe the formation of new topologically associating domains (‘neo-TADs’) caused by structural variants, group-specific 3D chromatin loops, and the replacement of CTCF insulators by DNA hyper-methylation. Through inhibition experiments, we validate that genes implicated by these 3D genome conformations are essential for the survival of patient-derived ependymoma models in a group-specific manner. Thus, this study extends our ability to reveal tumor-dependency genes by 3D genome conformations even in tumors that lack targetable genetic alterations.